Cuckoo algorithm with great deluge local-search for feature selection problems - Khalil Alsmadi, Mutasem; Alzaqebah, Malek; Jawarneh, Sana; Brini, Sami; Al-Marashdeh, Ibrahim; Briki, Khaoula; Alrefai, Nashat; Ali Alghamdi, Fahad; Al-Rashdan, Maen T. (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Feature selection problem is concerned with searching in a dataset for a set of features aiming to reduce the training time and enhance the accuracy of a classification method. Therefore, feature selection algorithms are proposed to choose important features from large and complex datasets. The cuckoo search (CS) algorithm is a type of natural-inspired optimization algorithms and is widely implemented to find the optimum solution for a specified problem. In this work, the cuckoo search algorithm is hybridized with a local search algorithm to find a satisfactory solution for the problem of feature selection. The great deluge (GD) algorithm is an iterative search procedure, that can accept some worse moves to find better solutions for the problem, also to increase the exploitation ability of CS. The comparison is also provided to examine the performance of the proposed method and the original CS algorithm. As result, using the UCI datasets the proposed algorithm outperforms the original algorithm and produces comparable results compared with some of the results from the literature.